Charting the aquaculture internet of things impact: Key applications, challenges, and future trend - Ahmad Fikri Abdullah; Hasfalina Che Man; Abdulsalam Mohammed; Murni Marlina Abd Karim; Suleiman Usman Yunusa; Nurshahida Azreen Binti Mohd Jais (Aquaculture Reports)
Aquaculture plays a pivotal role in global food production, grappling with distinct hurdles in water quality, feeding operation, and disease control. Efficient management of these core aquaculture operations has been acknowledged as a fundamental measure, yet remains unattainable through traditional methodologies. The advent of the Internet of Things (IoT) has opened up transformative avenues for real-time aquaculture operations. IoT solutions have emerged as a potent toolset, facilitating prompt monitoring, data collection, analysis, and control within aquatic environments. Notwithstanding its remarkable advantages, the technology is not devoid of limitations and areas requiring advancement. This paper examines the diverse applications of IoT in aquaculture, encompassing water quality monitoring, feeding strategies, and intelligent health inspection. Aquaculture challenges like sensor corrosion, data fusion limits, environmental impacts on transmission, and more have been thoroughly discussed. It also highlights IoT's potential in aquaculture, focusing on sensor advancements, artificial intelligent (AI) integration, and increased productivity. Presenting the IoT-aquaculture trajectory, this paper highlights IoT's potential in aquaculture while stressing the need to balance benefits with challenges.